2021
DOI: 10.1101/2021.11.25.21266863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Post-operative Pain in Lung Cancer Patients using Pre-operative Peak Alpha Frequency

Abstract: Aims and ObjectivesExperimental models of neuropathic pain suggest that individual peak alpha frequency (PAF), measured using electroencephalography (EEG), can predict future pain sensitivity in experimental settings. Here, we tested whether PAF could predict future pain severity in a clinical setting in patients undergoing thoracotomy.MethodsRecorded using wearable around the ear electrodes (cEEGrids), the feasibility and efficacy of pre-operative PAF as a neuro-marker for post-operative pain was assessed in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Nonetheless, the mixed findings could also arise from differences in methodological choices in the estimation of PAF e.g. frequency windows [39] and use of sensor vs. component space data [40] and estimation of CME e.g. map volume [21] vs. area [33].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the mixed findings could also arise from differences in methodological choices in the estimation of PAF e.g. frequency windows [39] and use of sensor vs. component space data [40] and estimation of CME e.g. map volume [21] vs. area [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown promise for a cortical biomarker pain signature involving two measures: peak alpha frequency (PAF), which is measured using resting-state electroencephalography (EEG) and refers to the dominant oscillatory frequency in the 8-12Hz range [4-6] and; corticomotor excitability (CME), which is measured using transcranial magnetic stimulation (TMS), and can be indexed as the volume of the primary motor cortex (M1) representation of a peripheral muscle [7]. Studies using pain models in healthy individuals have shown that PAF and CME can predict pain severity and duration [8-12]. One of these studies used intramuscular injections of Nerve Growth Factor (NGF), which produces progressively developing and clinically meaningful pain sustained over several days.…”
mentioning
confidence: 99%